ANTIVIRAL COATINGS TO PRODUCE BREATHABLE AND BIODEGRADABLE FILTER MASKS - da Cruz Paula, Rafael Santos; da Cruz Paula, Antônio; da Cruz Paula, Luis Felipe Santos; Gerardo, Camila Ferreira; Horta, Marco A. P.; Mares-Guia, Maria Angélica; Simão, Renata Antoun; de Lima, Luiz Carlos (Editora Impacto Científico, 2025)
Surgical masks are recommended by the World Health Organization for personal protection against disease transmission. However, most of the surgical masks on the market are disposable and cannot be self-sterilized for reuse. Thus, when confronting the global public health crisis, severe pollution due to disposable masks is inevitable. In this paper, a novel low-cost filter mask with excellent breathability is reported to replace the filters’ oil derivatives through an ecologically correct filter with properties sustainably optimized on a pre-industrial scale (roll-to-roll). A roll of common paper was passed through a vacuum chamber and deposited by CVD. Hydrophobicity and permeation were measured through contact angle, SEM and AFM. The droplets do not penetrate the filter for a minimum of two hours. Moreover, the filters proved to be efficient in antimicrobial and breathability tests. DOI: 10.56238/edimpacto2025.060-006